Nuances in Ksharasutra Preparation Using Guggulu Extract (International Journal of Ayurveda and Pharma Research, 2024)
Ano-rectal diseases are considered to be one of the conditions that affect a person's quality of life significantly. Ksharasutra (medicated thread) is a para-surgical procedure which is found more effective in the management of few among these conditions like fistula-in-ano and sinus. Ksharasutra is routinely prepared with Snuhi ksheera (latex of Euphorbia nerifolia), Apamarga Kshara (ash of Acyranthes aspera) and Haridra (powder of Curcuma longa). In conventional method, collection of Snuhi ksheera is time consuming, laborious and not available throughout the year. Here, Guggulu (Oleogum resin from Commiphora mukul) was selected as an alternative for Snuhi ksheera in the preparation of Ksharasutra as it is reported to have antiseptic, anti-inflammatory, wound-healing properties and it is available throughout the year. Guggulu was extracted using 95% ethyl alcohol, meanwhile Apamarga kshara was prepared in conventional way. Barbour linen thread no.20 was cut into 11 equal parts and mounted upon Ksharasutra frame. Each of which was later coated with 7,5,3 layers of Guggulu extract, combination with Apamarga kshara and combination with Haridra respectively. These were then kept under UV radiation in a cabinet and dried. After a speculated period of time the threads were cut down in a sterile condition, each (11 numbers) of them measuring 40 cm. These were then stored in an air-tight glass container. These Ksharasutras are prepared with a motive to get used in the management of the afore discussed ano-rectal conditions.